Improvement in estimating population mean using two auxiliary variables in two-phase sampling - Singh, Rajesh; Chauhan, Pankaj; Sawan, Nirmala; Smarandache, Florentin (Italian Journal of Pure and Applied Mathematics, 2011)
This study proposes improved chain-ratio type estimator for estimating population mean using some known values of population parameter(s) of the second auxiliary character. The proposed estimators have been compared with two-phase ratio estimator and some other chain type estimators. The performances of the proposed estimators have been supposed with a numerical illustration.